Chinese communication theory and research : reflections, new frontiers, and new directions - Jia, Wenshan, 1961-; Lu, Xing; Heisey, D. Ray (Advances in communication and culture., 2002)
A systematic examination of Chinese communication scholarship and comprehensive critique of its theories and methodologies are long overdue, and in this new collection of essays by a multicultural group of scholars, both aims are achieved. Focusing on such relatively new fields as Chinese health communication and Chinese communication on the internet, the volume addresses key questions about the state and the future of its field. Both challenging and complementing the Western views of communication, it advances theories of cultural and intercultural communication while at the same time broadening our understanding of the relevance of Chinese communication studies to communication studies overall, and the ways in which this subdiscipline points the way toward a new and more complicated future. The essayists, whose origins include the United States, Taiwan, Hong Kong, and China, bring their many perspectives to bear on what is the most comprehensive and inclusive review of Chinese communication research literature published in English. Of great benefit to Western and Eastern communication theorists, philosophers of social science, and Asian studies scholars, Chinese Communication Theory and Research is an invaluable guide to an increasingly complex and significant field of study.